2020
DOI: 10.3390/en13184663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of First Tower Earthing Resistance on Fast Front Back-Flashover in a 66 kV Transmission System

Abstract: Lightning stroke on a transmission tower structure is one of the major reasons that results in high voltages at the tower arms due to the excessive lightning current flowing through the transmission tower to earth. The Surge voltage seen at the tower cross arm on the first tower close to a substation is the worst case. If this voltage is higher than the withstand level of the insulator string, the insulation of substation equipment will be exposed to transient over-voltage called fast front back-flashover (FFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When calculating lightning surges arising on overhead power lines, the question often arises: how many towers should be taken into account? According to a review of publications [15] on this topic, it is necessary to take into account from 4 to 7 power transmission towers. To clarify the answer to this question using digitized oscillograms of real lightning currents, studies were carried out, the results of which are shown in Table 1.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…When calculating lightning surges arising on overhead power lines, the question often arises: how many towers should be taken into account? According to a review of publications [15] on this topic, it is necessary to take into account from 4 to 7 power transmission towers. To clarify the answer to this question using digitized oscillograms of real lightning currents, studies were carried out, the results of which are shown in Table 1.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…EMTP can be projected to analyze transients on circuits containing concentrated parameters (R, L, and C), transmission lines with distributed parameters, and line with no transposition. Phase conductors and shielding cables are modeled based on tower data [26], [38]- [41]. A brief outline of the EMTP-ATP model used purposely for this paper is presented in the form of a model consisting of several components [42]- [45]: i) generator, ii) phase conductors of transmission lines and shielding cables including line termination and power frequency voltage, iii) transmission line tower, iv) tower grounding impedance, v) string insulator (i.e.…”
Section: Transient Program (Emtp)mentioning
confidence: 99%
“…The grounding grid is an important component for lightning protection [1,2]. The transient performance of grounding system has been a hot topic for a long time [3][4][5].…”
Section: Introductionmentioning
confidence: 99%